HUBUNGAN PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) DINI DENGAN KEJADIAN DIARE PADA BAYI USIA 0-6 BULAN - Harahap, Nuraisyah; Indriati, Ganis; Dewi, Wan Nishfa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Diarrhea is basically the frequency of defecation more than 4 times in infants and more than 3 times in children (more often than usual) with more watery consistency. Diarrhea can be caused by many factors and babies have been fed other than breast milk or complementary foods before 6 months of age. This study aims to determine relationship between the provision of early breastfeeding complementary foods with the incidence of diarrhea in infants aged 0-6 months. This research was conducted in the working area of Rejosari Pekanbaru Health Center. This research used descriptive correlation research design and cross sectional approach. The study sample was 92 respondents taken based on inclusion criteria using cluster sampling techniques. The measuring instrument used questionnaire. The analysis used is univariate analysis to determine the frequency distribution and bivariate using Chi Square. The study found 69 respondents who were given complementary food early ASI (75.0), and 56 people (60,9%) infants who had diarrhea. Chi Square results obtained p value = 0.001 <a (0.1) and it can be concluded that there is a significant relationship between the provision of early breastfeeding complementary foods and the incidence of diarrhea. The results of this study recommend to mothers who have babies aged 0-6 months to continue to give exclusive breastfeeding to their babies without providing additional food to the baby, so the baby is protected from diarrheal disease.Keywords : Baby, complementary foods, diarrhea,